Cyclic deformation and lattice strain distribution of high Nb containing TiAl alloy. Issue 14 (21st September 2020) - Ding, Jie; Shi, Shan; Dong, Zhili; Lin, Junpin; Ren, Yang; Wu, Xiaodong; Chang, Hui; Zhou, Lian
Abstract : Low cycle fatigue of lamellar TiAl with 8.5 at.-%Nb was studied with a total strain amplitude of 0.28% at three temperatures: room temperature, 750°C and 900°C. At room temperature, the material exhibited cyclic hardening and the fracture mode was mainly interlamellar. At 750°C and 900°C, the material showed cyclic softening and the fracture mode was translamellar. The lattice strain in γ phase was almost tensile and larger tensile lattice strain in γ phase seems detrimental. Besides, the opposite direction of 201γ and 100α2 lead to crack propagation along α2 /γ interfaces. B2/βo phase always suffered compressive lattice strain in the tests. The destruction of lamellar microstructure was the reason for colony refinement at 750°C and 900°C.